PENGARUH KONSENTRASI KEPEMILIKAN DAN ASIMETRI INFORMASI TERHADAP UNDERPRICING SAHAM PADA SAAT INITIAL PUBLIC OFFERING (IPO) DI BURSA EFEK INDONESIA - Rahmah Fardila; Syarifah Rahmawati (Departemen Manajemen, 2019)
The purpose of this study was to analyze the effect of internal ownership concentration and information asymmetry of the underpricing of shares in an Initial Public Offering (IPO) in the Indonesia Stock Exchange (IDX). This study used a purposive sampling technique with certain criteria, and obtained 93 samples of 155 companies who was listed in the Indonesia Stock Exchange (IDX) in 2008-2017. The method of analysis used in this study was the method of multiple linear analysis (Multiple Linear Regression). The results showed that: (1) the ownership concentration has negative and significant effect to Underpricing,. Where the market can find out the high concentration of ownership when the IPO is something that is not too attractive for investors. Majority shareholders try to increase proceedings by making prices higher during the IPO. (2) Information Asymmetry has a significant and significant effect on Underpricing, where illiquid stocks must compensate in the form of a high rate of return.